2021
DOI: 10.21037/tgh-2019-ie-07
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endoscopic resection: a review of endoscopic submucosal dissection (ESD), endoscopic full thickness resection (EFTR) and submucosal tunneling endoscopic resection (STER)

Abstract: Subepithelial lesions are often detected incidentally in patients undergoing an endoscopy. They are common tumors of the gastrointestinal (GI) tract which can originate from different layers of the GI tract wall. These lesions can be further classified based on GI layer of origin and unique histochemical staining. While most are benign and asymptomatic, some of these lesions have malignant potential with distant metastases. However, current diagnostic modalities including endoscopy with biopsy or endoscopic ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…1,3 Over-the-scope clip-assisted EFTR has been deemed suitable for lesions that are ,2 cm in the colorectum. 5 One multicenter prospective study demonstrated that the FTRD device had an overall technical efficacy of 89.5% and an R0 resection rate of 76.9%. 6 In this study, lesions ,2 cm had an R0 rate of 81.2% while lesions .2 cm had an R0 rate of 58.11%.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Over-the-scope clip-assisted EFTR has been deemed suitable for lesions that are ,2 cm in the colorectum. 5 One multicenter prospective study demonstrated that the FTRD device had an overall technical efficacy of 89.5% and an R0 resection rate of 76.9%. 6 In this study, lesions ,2 cm had an R0 rate of 81.2% while lesions .2 cm had an R0 rate of 58.11%.…”
Section: Discussionmentioning
confidence: 99%